Surface Properties of Ti65Zr Alloy Modified with TiZr Oxide and Hydroxyapatite - Elinor Zadkani Nahum; Alex Lugovskoy; Svetlana Lugovskoy; Alexander Sobolev (Nanomaterials, 2023)
Titanium-zirconium dioxide nanostructures loaded by hydroxyapatite were produced on the surface of Ti65Zr alloy. The alloy was treated by anodization with the subsequent immersion in calcium glycerophosphate (CG) solutions. The resulting surfaces present TiO2-ZrO2 nanotubular (TiZr-NT) structures enriched with hydroxyapatite (HAP). The nanotube texture is expected to enhance the surface’s corrosion resistance and promote integration with bone tissue in dental implants. The TiZr-NT structure had a diameter of 73 ± 2.2 nm and a length of 10.1 ± 0.5 μm. The most favorable result for the growth of HAP in Hanks’ balanced salt solution (Hanks’ BSS) was obtained at a CG concentration of 0.5 g/L. Samples soaked in CG at a concentration of 0.5 g/L demonstrated in a decrease of the contact angles to 25.2°; after 3 days of exposure to Hanks’ BSS, the contact angles further reduced to 18.5°. The corrosion studies also showed that the TiZr-NT structure soaked in the CG = 0.5 g/L solution exhibited the best corrosion stability.